Ethnomedicine Study on Justicia gendarussa for Male Contraception at the Nimboran Ethnic, Jayapura - Niluh Indrawati; Retno Widyowati; Pilipus Kopeuw; Bambang Prajogo Eko Wardoyo (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Justicia gendarussa from Papua has traditionally been used for the treatment of several diseases, and phytochemical studies have been carried out since 1987. Objective: This study aimed to determine the use of this plant as a male contraceptive that the Nimboran Ethnic and their perspectives have long used. Method: A qualitative method with an ethnographic approach was used, while data were collected through interviews, observations, and documentation. The informants were selected using purposive and snowball sampling. Result: The results showed that 44% of people use it to delay pregnancy, 24% due to young marriage with poor economic conditions, 14% after moving to another place 12% because of tribal wars over fertile land to multiply offspring. The preparation and usage of this plant through the collection, mixing, and manufacturing method and in terms of dosage, time, and duration of use were explored more deeply by conducting interviews with 50 informants. The effectiveness and success as a method of contraception are presented in the way the community has known the plant over different generations, and this method is still used as an alternative option considering the very wide area profile from one place to another. Conclusion: Justicia gendarussa is used by the Nimboran Ethnic group as an ingredient in traditional medicines, especially for male contraception.